Наша восемнадцатая осень - Внуков Николай Андреевич (Лениздат, 1990)
Экземпляры: ф.2 (1991) / Инвентарный номер: 22316 / Цена: 2.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 60 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6